Personalist rule in Africa and other world regions - Bosch, Jeroen J. J. van den (Routledge studies in African politics and international relations, 2021)
Introduction -- A Throne of Bayonets - What is Personalism and Why Does it Matter? -- Fear & Greed - Four Pillars of Personalist Regime Behavior -- Framing The Vicious Circle - Modeling Transitions from Personalist Rule -- Divide & Rule - Testing the Relational Aspects of the Model -- Resource Curses - Testing the Functional Aspects of the Model -- Votes & violence - Testing the Dysfunctional Aspects of the Model -- Findings on the Impact of Personalist Rule - Comparing African Cases and Structuring Causal Factors -- Findings on Vicious Circles - Comparing Post-Personalist Transitions -- Lessons From Africa - Personalism in Comparative Perspective -- Summary and Final Thoughts.